1995
DOI: 10.1093/ajcp/104.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Bone Marrow Nucleated Cell Counts for the Presence of Fat Particles

Abstract: Although the use of bone marrow transplantation has increased greatly in recent years, the quality control procedures used in bone marrow processing laboratories remain less than ideal. Accurate marrow total nucleated cell (TNC) counts are essential for effective monitoring of bone marrow collection and processing. Aspirated marrow is variably contaminated by fat particles, resulting in overestimation of marrow TNC by automated analyzers. A recently-marketed hematological analyzer (Cobas-Helios; Roche Diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The recently developed CD4000 hematology analyzer can detect erythroblasts, and use of this hematology analyzer to estimate bone marrow cellularity has been found to be successful [6, 7]. Another advantage of the use of this analyzer is that it can eliminate fat particles, since they distributed to a different area on the scattergram [6], and thus treatment to remove them is not necessary, as it is with other instruments [3]. In this study, we attempted to determine the ability of the CD4000 to analyze bone marrow aspirates for more detailed examination, since the cell clusters on the scattergram could be visually differentiated into several groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently developed CD4000 hematology analyzer can detect erythroblasts, and use of this hematology analyzer to estimate bone marrow cellularity has been found to be successful [6, 7]. Another advantage of the use of this analyzer is that it can eliminate fat particles, since they distributed to a different area on the scattergram [6], and thus treatment to remove them is not necessary, as it is with other instruments [3]. In this study, we attempted to determine the ability of the CD4000 to analyze bone marrow aspirates for more detailed examination, since the cell clusters on the scattergram could be visually differentiated into several groups.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte analysis of peripheral blood is now possible with automated hematology analyzers that can provide accurate and precise data in a very short time. Trials to analyze bone marrow aspirates by such automated hematology analyzers have been performed for years, but there was a limitation for such application, since hematology analyzers based on the impedance principle are incapable of accurate enumeration of erythroblasts and therefore include them when counting the lymphocyte fraction [1, 2, 3]. Also, it has been difficult to exclude interfering substances in bone marrow aspirate.…”
Section: Introductionmentioning
confidence: 99%
“…Some attempts have been made to apply automated blood cell counters to bone marrow aspirate measurement (1)(2)(3)(4), with an increasing number of reports being presented especially after the appearance of blood cell counters capable of NRBC counting. However, satisfactory results have yet to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…If analysis of bone marrow is possible with automated hematology analyzers, then faster and more objective examination will be possible. Trials of analysis of bone marrow aspirates have been reported with several automated hematology analyzers (1)(2)(3)(4), but sufficient accuracy has not been obtained due to various technical problems. Major problems have included failure to count nucleated red blood cells (NRBCs), difficulty in correctly differentiating various immature cells, and interference by lipid in bone marrow.…”
mentioning
confidence: 99%
“…Automated quantitative analysis of bone marrow cellular composition by hematology analyzers, however, has always been difficult [1][2][3]. A number of problems, in fact, arise from difficulty in erythroblast identification, contamination by fat particles, heterogeneity of cell types and maturation levels, and the presence of low-frequency and very large cells.…”
Section: Introductionmentioning
confidence: 99%